Pengaruh Kompetensi, Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Panca Kharisma Utama - Rusna Hayati; Nazifah Husainah; Cecep Haryanto; M. Yusuf (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to know and analyze the influence of Competence, Organizational Culture and Work Motivation to Employee Performance Variable at PT Panca Kharisma Utama. The independent variables used are Competence, Organizational Culture and Work Motivation, while the dependent variables are Employee Performance. The data collection method in this research was carried out by distributing questionnaires to 60 respondents from PT. Panca Kharisma Utama. The research method used is a quantitative method that is associative in nature using primary data. and the data analysis model used is adalah IBM Statistical Product and Service Solutions (SPSS) 27. The results of this research show Competence,has a positive and significant effect on employee performance with a coefficient value of “0,134”, Organizational Culture has a positive and significant effect on Employee Performance with a coefficient value of “0,535”, Work Motivation has a positive and significant effect on Employee Performance with a coefficient value of “0,126”, and Competence, Organizational Culture and Work Motivation has a positive and significant effect on employee performance with a coefficient value of “0,885” .